2017
DOI: 10.1111/jnc.13978
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of nebivolol against cisplatin‐associated depressive‐like behavior in rats

Abstract: One-third of cancer patients undergoing chemotherapy treatment often display symptoms of depression leading to poor adherence and decreased quality of life. Thus, this study aimed to investigate the possible protective effect of nebivolol against cisplatin-associated depressive symptoms in adult male rats. Nebivolol is a highly cardioselective β-adrenergic receptor blocker that possesses endothelium-dependent vasodilator properties and antioxidant capacities. Animals were allocated into four groups. Group one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 55 publications
(90 reference statements)
2
17
3
Order By: Relevance
“…Behavioral and neurological functions were assessed for all animal groups via performing open field and Garcia neurobehavioral tests, respectively. Open field test measures the locomotor activity of the rats by measuring their ambulation frequency in a given field for 3 min [22,23]. Additionally, Garcia neurobehavioral test measures neurological defect by scoring six individual tests evaluating spontaneous activity, symmetry in the movement of the four limbs, forepaw outstretching, climbing, body proprioception, and response to vibrissae touch [24].…”
Section: Assessment Of Behavioral and Neurological Functionsmentioning
confidence: 99%
“…Behavioral and neurological functions were assessed for all animal groups via performing open field and Garcia neurobehavioral tests, respectively. Open field test measures the locomotor activity of the rats by measuring their ambulation frequency in a given field for 3 min [22,23]. Additionally, Garcia neurobehavioral test measures neurological defect by scoring six individual tests evaluating spontaneous activity, symmetry in the movement of the four limbs, forepaw outstretching, climbing, body proprioception, and response to vibrissae touch [24].…”
Section: Assessment Of Behavioral and Neurological Functionsmentioning
confidence: 99%
“…One of the most recently reported manifestations of adverse effect of cisplatin on CNS has clinical form with characteristics of increased depressive state level (30). The prodepressant action of cisplatin, by means of behavioral tests results, in that study (performed on rats) was accompanied with prooxidant alterations in both cortex and hippocampus.…”
Section: Discussionmentioning
confidence: 79%
“…The prodepressant action of cisplatin, by means of behavioral tests results, in that study (performed on rats) was accompanied with prooxidant alterations in both cortex and hippocampus. Also, neuronal degeneration in hippocampus paralleled the decline in BDNF and GABA content, as well as the increase in hippocampal glutamate (30).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In humans, neurotoxicity is usually manifested by peripheral nerves dysfunction and sensory disorders, seizures, reduced cognitive abilities and various mood disorders (8,9). Studies performed on animal experimental models confirmed cisplatin-induced neurotoxicity by means of motor impairment (10), decline of cognitive functions (11), mood disorders (12) and alterations in nociception (13).…”
Section: Introductionmentioning
confidence: 99%